A novel child-centred core palliative care outcome measure for use in clinical practice and research: findings from a multinational validation study - Namisango, Eve; Murtagh, Fliss E M; Bristowe, Katherine; Downing, Julia; Powell, Richard A; Atieno, Mackuline; Sandham, Margaret; Ali, Zipporah; Meiring, Michelle; Mwangi-Powell, Faith N; Abbas, Melanie; Fraser, Lorna K; et al. (BioMed Central Ltd, 2025)
Outcome measurement is pivotal to person-centred assessment, quality improvement and research. Children and young people with life-limiting and -threatening illness have high needs and service use, yet there is a lack of evidence for interventions and care models. Efforts to strengthen paediatric palliative care (PPC) services has been hampered by the lack of an appropriate outcome measure. To determine the validity, reliability, measurement invariance, responsiveness, acceptability, and interpretability properties of the novel Children's Palliative care Outcome Scale (C-POS). We recruited children (0-17 years) with life-limiting/life threatening conditions and their families in Kenya, Uganda and South Africa. Using C-POS repeated measurement using over four timepoints. We assessed: 1) construct validity (structural properties, discriminant validity, known groups validity, measurement invariance, differential item functioning by country), 2) reliability (internal consistency and test re-test), 3) responsiveness, 4) acceptability (time to complete) and 5) interpretability. We recruited a cohort of 434 children (response rate 94%). Of these, 302 participated in the repeated measures component and 279 (92%) completed four datapoints. We found evidence for face and content validity as the C-POS items mapped on to themes developed from qualitative interviews, including: pain and other symptoms, pyscho-social well-being, and family wellbeing that matter to children and their families. We confirmed: 1) the two-factor structure (child and family subscales). We also confirmed discriminant and known groups validity, as well as construct equivalence for the child self-report and proxy versions. Controlling for age, we found no differential item functioning by country setting. 2)The sub-scale internal consistency was moderate, given the multi-dimensional nature of the C-POS self and proxy report versions omega scores (0.67 and 0.73, respectively). The test characteristic curve information confirmed the moderate internal subscale consistency scores between 0.3- 0.9 for the proxy version and 0.3-0.5 for the self-report version. Test-retest reliability was acceptable for all items, with weighted kappa range for scores: self-report (0.43-0.57) and proxy version (0.35-0.64) and family items (0.51-0.71). 3)Responsiveness was demonstrated, except for the feeding item. 4)Median completion time at the last visit was 10 min for both versions with minimal missing data. 5)The minimum important difference was 3 for the self and proxy report versions on a scale of 0-30 and 4 for the child and family scale on a scale of 0-55. The C-POS has good psychometric properties. To further improve the measure, we identified items for potential removal, conceptual gaps that should be addressed and domains for which developmental age-appropriate items are needed. C-POS has potential to evaluate and improve person-centred children's palliative care in research and routine clinical practice. MEDLINE